Analysis and Design in Kuningan Regency: Study Case Of The Road Section Of Sukadana Kuningan - Karangwuni Cirebon - Taruna, Ghilang Alfy; Harianti, Mira Lestira (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
Kuningan Regency is one of the areas that has tourism potential with mountainous geographical conditions with various natural beauties and natural springs. Therefore, Kuningan Regency requires good and planned management in order to achieve optimal results. One of the supporting facilities for tourism in Kuningan Regency is road access that must be developed. In supporting the Government Program related to Regional Development Potential and in accordance with the Regional Spatial Plan of Kuningan Regency Year 2011-2031 regarding the development of road networks to support the tourism sector. So it is necessary to plan road development, which is intended to facilitate relations from one region to another. Where the Road Network has a very important function, namely as a transportation infrastructure in the accessibility and mobility of goods and services which is the lifeblood for encouraging economic growth, social, cultural and national stability, as well as efforts to equalize and spread the building.On the horizontal alignment of the Sukadana Kuningan - Karangwuni Cirebon road section there are 8 bend points. Including 6 Full-Cricle bend points and 6 Spiral-Circle-Spiral bend points. The vertical alignment of the Sukadana Kuningan - Karangwuni Cirebon road section has 22 arch points consisting of 11 concave vertical points and 13 convex vertical points. Making vertical arches aims to balance the number of excavations and embankments at the existing location. The amount of excavation in this road section plan is 530656.5m3 while the amount of embankment is 1859787.22m3.. The type of pavement used is flexible pavement with a thickness of 40 cm top grade LPA, 6 cm AC-BC and 4 cm AC-WC. There is 1 bridge with a length of 80 m. The construction of the Ciawigebang Ring Road section in Kuningan Regency costs Rp. 351,385,080,000.00, - (THREE HUNDRED FIVE HUNDRED ONE MILLION THREE HUNDRED EIGHTEEN THOUSAND FIVE MILLION EIGHT HUNDRED THOUSAND THOUSAND RUPIAH). and can be completed within 1 year.